Tetranuclear manganese (III) salicylaldoxime ensemble - Kumbhar, Avinash S.; Mulay, Mahesh P.; Padhye, Subhash B.; Tavale, Sudam S.; Puranik, Vedavati G. (Structural Chemistry, 2008)
Crystal structure of {[Mn(salicylaldoximeH)(salicylaldoxime)](4)} center dot 3CHCl(3) 1 formed by the interaction of MnCl2 center dot 4H(2)O and salicylaldoxime in a 1:1 ratio is described. The compound crystallizes in the orthorhombic space group Pbca (No 61) with the lattice parameters; a = 27.769 (3), b = 22.672 (2), c = 21.650 (2) angstrom, V = 13630 (2) angstrom(3), Z = 8, R-1 = 0.0776, wR(2) = 0.2356, S = 1.164. The cluster with four Mn (III) centers formed by four terminal and four bridging salicylaldoxime ligands results in a central rotating wheel-like core with the Mn-Mn separation varying from 3.531 to 3.576 angstrom and with the diagonal distances being 4.156-4.165 angstrom. Four intramolecular H-bonds between a terminal oxime (NOH) group and the adjacent phenolate oxygen atom of another ligand stabilize the structure of the cluster. Spectral, magnetic, and cyclic voltammetry studies corroborate a stable Mn (III) tetramer.